Public debt, institutional quality and economic growth in sub-Saharan Africa - Sani, Abdullahi; Said, Rusmawati; Ismail, Normaz Wana; Mazlan, Nur Syazwani (University of Malaya, 2019)
While other regions with better institutional quality have benefitted considerably from borrowing, sub-Saharan Africa continues to accumulate public debt with a long history of dismal economic performance. This paper examines the impact of public debt and institutional quality on economic growth using the Generalised Method of Moments (GMM) approach on a sample of 46 sub-Saharan African countries over the period 2000–2014. The empirical result indicates that institutional quality has both a direct and indirect impact on economic growth and therefore reveals that the interaction term of institutional quality and public debt has a statistically significant impact on the debt-growth relationship. This confirms the hypothesis that the impact of public debt on economic growth is a function of institutional quality. Moreover, government effectiveness, control of corruption and regulatory quality were found to have the strongest influence in mitigating the negative impact of public debt on economic growth in sub-Saharan Africa. Therefore, comprehensive improvement of the institutional quality is necessary not only in minimising the negative impact of public debt but also in delivering the unwavering benefits of government borrowing.